2012
DOI: 10.1155/2012/809682
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Intentions and Interest in Integrated Family Planning Services among Women Living with HIV in Nyanza Province, Kenya: A Qualitative Study

Abstract: Despite increasing efforts to address the reproductive health needs of people living with HIV, a high unmet need for contraception exists among HIV+ women in sub-Saharan Africa. This study explores the fertility intentions and family planning (FP) preferences of Kenyan women accessing HIV treatment. We conducted 30 semistructured interviews and qualitatively analyzed the data with a grounded theory approach. Fears of premature death, financial hardship, and perinatal HIV transmission emerged as reasons for par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 23 publications
4
57
0
Order By: Relevance
“…Efforts toward integrating FP counselling and services into HIV clinical care have improved uptake of dual method use, 283242 but there are substantial barriers to FP/HIV integration such as different funding streams resulting in vertical programming both at the policy and clinic level, inadequate training of HIV providers in reproductive health and contraceptive method choice counselling, and restricted availability of contraceptives at HIV clinics. 3443 Because condom use was lower among men and women using highly effective contraception, programmes should also ensure that appropriate messages and access to condoms continue to be reinforced.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts toward integrating FP counselling and services into HIV clinical care have improved uptake of dual method use, 283242 but there are substantial barriers to FP/HIV integration such as different funding streams resulting in vertical programming both at the policy and clinic level, inadequate training of HIV providers in reproductive health and contraceptive method choice counselling, and restricted availability of contraceptives at HIV clinics. 3443 Because condom use was lower among men and women using highly effective contraception, programmes should also ensure that appropriate messages and access to condoms continue to be reinforced.…”
Section: Discussionmentioning
confidence: 99%
“…The present study emerged out of previous qualitative work during the cluster-randomised trial among HIV care providers and women and men living with HIV. Our previous studies raised many questions about relationship power dynamics and socio-cultural gender norms as factors in contraceptive access—factors that could not be addressed with interventions to improve health systems such as in the integration trial (Harrington et al 2012; Newmann, Mishra et al 2013). We sought to gain greater insight into couple decision-making and relationship power concerning fertility and family planning, in order to inform interventions targeting men and couples in the setting of high HIV prevalence.…”
Section: Methodsmentioning
confidence: 99%
“…A qualitative study among HIV-infected women in Nyanza showed that perceptions about side effects of contraceptive methods strongly influenced HIV-infected women’s choices along with access to FP and partners’ resistance to contraceptive use. 9 …”
Section: Introductionmentioning
confidence: 99%